The administration of physical education, sport, and leisure programs - Tillman, Kenneth G.; McCue, Betty Foster.; Esslinger, Arthur A.; Voltmer, Edward F. (Allyn and Bacon, 1996)
This book is about: Administrative and management concepts; management responsibilities; Program administration; ...